Effects of Seed density on Grain yield and Agronomic traits of Wheat (Triticum aestivum L.) under Kabul and Khost Agro-Ecological conditions, Afghanistan - Ahmadi, Ahmad Yar; Salari, Mohammad Wali; Arian, Mohammad Jan; Asim, Abdul Mosawer (International Journal of Scientific Research in Biological Sciences, 2021)
Optimum seed density is an important factor for high yield as well as wheat grain quality. Apt seed density not only increases yield but reduces the total cost of wheat production. The purpose of this research was to investigate the most optimum density for three wheat varieties under two different environments to produce high yield of wheat. The experiment was conducted in two different agro-ecological zones (Kabul and Khost provinces, Afghanistan) during the 2018 - 2019 growing season. The research was arranged in Randomized Complete Block Design with the combinations of densities (100, 110 and 120 kg ha-1) and three wheat varieties (Baghlan09, Kabul013 and Moqawim09). Densities and varieties revealed significant differences for different traits under study. Results indicated that Kabul013 and Baghlan09 at 110 kg seeds ha-1 in zone 1 had better fertile tillers, spike length and grain yield while the same varieties in zone 2 performed better at 120 kg ha-1 for these traits. Interestingly Moawwim09 produced better of these traits on120 kg ha-1in both zones. Interaction effects among the locations, densities x variety were also significant. From the analysis results, it’s concluded that 110 kg seeds ha-1 for Kabul013 and Baghlan09 varieties and 120 kg seeds ha-1 for Moqawim09 variety in zone 1 while 120 kg seeds ha-1 for all three varieties in zone 2 are the suitable seed rate and should be sown